Effect of Workload, Work Shift, and Work Stress on Burnout of General Practitioners at Makassar Regional General Hospital during the COVID-19 Pandemic - Suharni, Suharni; Ihksan Agus, Al; Samsualam, Samsualam; Baharuddin, Alfina (Gaceta Médica de Caracas, 2023)
Objective: This study aimed to analyze the relationship between workload, work shifts, work stress, and work fatigue in general practitioners at Makassar Regional General Hospital. Method: This research used an analytical observational method with a cross-sectional study design. The sampling method used total sampling on general practitioners at Makassar Regional General Hospital. Workload, work shifts, work stress, and work fatigue were measured using questionnaires.